Development and psychometric evaluation of the Japanese version of the Nurse Professional Competence Scale Short-Form - Tanabe, Sachiko; Tanaka, Mika; Arai, Yoko; Matsuo, Kanae; Nakrem, Sigrid; Gardulf, Ann (Belitung Nursing Journal, 2025)
Background: To develop high-quality human resources with the competence required for nursing, contents of undergraduate education programs must be reviewed and enhanced. Assessments of competence levels at the time of graduation can be used to evaluate nursing education programs. International comparisons using a common assessment instrument can help identify and endorse common features, as well as highlight areas that need reform in nursing education programs from a wide range of perspectives. Objective: To develop the Japanese version of the Nurse Professional Competence Scale Short-Form and assess its psychometric properties. Methods: This study used a descriptive cross-sectional design to validate an instrument, conducted at eight university schools of nursing in mainland Japan. A total of 714 graduating nursing students were invited and informed about the study in mid-February 2022, with 299 students (41.88%) responding to all questions and submitting their answers via online survey forms. After item analysis, confirmatory factor analysis was conducted. Concurrent validity and internal consistency were also assessed. Results: Respondent ages ranged from 21 to 51 years, with an average age of 22.4 ±1.97 years. Most of the respondents were female (97.99%). The mean score for the scale was 55.70 (±9.98), and the scores for the six competence areas ranged from 48.04 (±14.07) to 64.73 (±10.67). Item analysis revealed that all items met each criterion, except for Pearson’s correlation coefficients for Items 34 and 35. Confirmatory factor analysis showed the CMIN/df value was 2.46, and the root mean square error of approximation value was 0.07. Concurrent validity analysis showed significant moderate correlations (r = 0.45 and 0.49, p < 0.001). The Cronbach’s α values for the scale and six competence areas ranged from 0.75 to 0.95.Conclusions: The Nurse Professional Competence Scale Short-Form Japanese version, comprising 35 items across six competence areas, demonstrated reasonably acceptable validity and reliability for use with graduating nursing students in Japan. The highest- and lowest-scoring competence areas were Value-Based Nursing Care and Medical Technical Care, respectively.